Real-time X-ray scattering studies of film evolution in high performing small-molecule–fullerene organic solar cells12. Issue 16 (28th April 2015) - Engmann, Sebastian; Bokel, Felicia A.; Herzing, Andrew A.; Ro, Hyun Wook; Girotto, Claudio; Caputo, Bruno; Hoven, Corey V.; Schaible, Eric; Hexemer, Alexander; DeLongchamp, Dean M.; Richter, Lee J.
<x xml:space="preserve">Abstract</x> Comprehensive studies of the influence of the formulation additive 1, 8-diiodooctane on the structural evolution of small molecule BHJ films with GIWAXS and GISAXS are presented.